Pembuatan Prototipe dan Analisis Unjuk Kerja Mekanis Perahu Otonom Propulsi Tenaga Angin - Setiawan, Joga; Saputro, Rohman; Iskandar, Norman; Paryanto, P (ROTASI, 2022)
Wind power propulsion autonomous boat (POPTAN) is a robotic boat that moves by utilizing wind energy through the automatic control of its sails and rudders. POPTAN can be used as an ocean monitoring tool with the advantage of operating autonomously for a relatively long period. In this study, the POPTAN has a main wing and a flap to adjust the angle of attack of the main wing, the steering section to determine the direction, and the keel section to maintain stability. A dynamic simulation model of POPTAN with MATLAB was made to assess the response of the speed and direction of the boat motion, with a specific flap angle flap and rudder angle, constant wind speed, and calm seawater conditions. Measurements and calculations of the non-essential mass added to the boat were carried out. The roll and pitch motion testings were performed by varying the wind speed by 4, 6, 8, and 10 m/s for two keel configurations. It is concluded that the greater the wind speed, the higher the response speed, the higher the steady-state speed in the resultant direction dominated by the longitudinal axis direction velocity, and the steady-state angle of motion the boat will be smaller. The boat can carry non-essential mass up to 4.5 kg. In the roll motion test, the results of the 2nd keel showed better performance than the 1st keel, based on the value of the oscillation period and damping constant.